The role of radical prostatectomy in high-risk localized, node-positive and metastatic prostate cancer. (March 2016) - Ristau, Benjamin T; Cahn, David; Uzzo, Robert G; Chapin, Brian F; Smaldone, Marc C
A lack of quality evidence comparing management strategies confounds complex treatment decisions for patients with high-risk prostate cancers. No randomized trial comparing surgery to radiation has been successfully completed. Despite inherent selection biases, however, observational and registry data suggest improved outcomes for patients initially managed with prostatectomy. As consensus shifts away from aggressive treatment for low-risk disease and toward multimodal treatment of locally advanced and metastatic disease, there is renewed interest in surgery for local control in patients presenting with high-risk localized, node-positive and minimally metastatic disease. The objective of this review is to examine the evidence evaluating clinical outcomes of patients with high-risk clinically localized, node-positive and metastatic prostate cancer treated with radical prostatectomy.